2007
DOI: 10.1002/pmic.200601053
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of N‐glycosylation in mosquito dopachrome conversion enzyme

Abstract: A novel dopachrome conversion enzyme (DCE) is present in insects and involved in their melanization pathway. DCE shares no sequence homology with any noninsect species from bacteria to humans. Several DCE sequences have been available, but enzyme structure and catalytic mechanism are unclear. This study concerns DCE PTMs, especially glycosylation. A mosquito DCE was purified and its monosaccharide composition, N-glycosylation site, and oligosaccharide structures were determined. Results showed that N-acetyl D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…A similar protein, which accelerates the melanization process, has also been reported in other insect species (Aso et al, 1984). Based on its function, a mosquito enzyme for melanization was discovered and named dopachrome conversion enzyme (DCE) (Li et al, , 2007.…”
Section: Insect Melanizationmentioning
confidence: 76%
“…A similar protein, which accelerates the melanization process, has also been reported in other insect species (Aso et al, 1984). Based on its function, a mosquito enzyme for melanization was discovered and named dopachrome conversion enzyme (DCE) (Li et al, , 2007.…”
Section: Insect Melanizationmentioning
confidence: 76%
“…By lectin-binding assay, the authors detected the presence of α -D-mannose, α -D-N-acetyl-galactosamine, β -D-gal-(1,3) N-acetyl-galactosamine, β -D-galactose, N-acetyl-galactosamine, α -L-fucose, and β -N acetyl-glucosamine. Likewise, different oligosaccharide structures such as Man3GlcNAc2, Man3 (Fuc) 1-2GlcNAc2 were detected [ 55 ]. Recently, Francischetti et al [ 56 ] demonstrated the presence of sulfated glycans in the salivary gland of Anopheles gambiae .…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has confirmed that of the 13 Drosophila yellow family genes, yellow‐f, and yellow‐f2 produce enzymes with DCE activity (Han et al ., ). We have also characterized a DCE from the yellow fever mosquito A. aegypti (Johnson et al ., ; Li et al ., ). Although, the functions of many remaining yellow genes still remain uncharacterized, it is likely that they are also involved in melanization or sclerotization pathways (Ferguson et al ., ).…”
Section: Melanization Enzymesmentioning
confidence: 97%